2016
DOI: 10.1016/j.ebiom.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The miR-367-3p Increases Sorafenib Chemotherapy Efficacy to Suppress Hepatocellular Carcinoma Metastasis through Altering the Androgen Receptor Signals

Abstract: The androgen receptor (AR) was found to suppress hepatocellular carcinoma (HCC) metastasis at late stages. Due to this discovery, we searched for some AR enhancers to increase the efficacy of Sorafenib chemotherapy, and identified the microRNA (miR)-367-3p, whose expression is positively correlated with AR expression in advanced HCC, as an HCC metastasis suppressor. Combining miR-367-3p with Sorafenib showed better efficacy to suppress HCC cell invasion in vitro and in vivo. Mechanism dissection revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 55 publications
(67 reference statements)
4
57
0
Order By: Relevance
“…Currently, an increasing number of studies have suggested miR‐367‐3p is a critical cancer‐related miRNA that is dysregulated in a wide range of cancers . However, whether miR‐367‐3p is dysregulated in cervical cancer and, further, participates in the progression of cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, an increasing number of studies have suggested miR‐367‐3p is a critical cancer‐related miRNA that is dysregulated in a wide range of cancers . However, whether miR‐367‐3p is dysregulated in cervical cancer and, further, participates in the progression of cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an increasing number of studies have suggested miR-367-3p is a critical cancer-related miRNA that is dysregulated in a wide range of cancers. [25][26][27][28] However, whether miR-367-3p is dysregulated in cervical cancer and, further, participates in the progression of cervical cancer remains unclear. The present study was aimed to investigate the expression status and biological function of miR-367-3p in cervical cancer and elucidate the potential underlying mechanism of miR-367-3p action.…”
mentioning
confidence: 99%
“…Depending on their mRNA targets, miRNAs can act as oncogenes or tumor suppressor genes. 26,27 The changes of miRNA are involved in most aspects of cancer biology, including proliferation, apoptosis, migration, and invasion. [28][29][30] Therefore, miRNAs are usually viewed as a potential diagnostic and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR‐193b has been shown to specifically sensitize HBV‐infected HCC cells to sorafenib and full‐length hepatitis C virus reportedly increases its expression . Moreover, miR‐486 and miR‐367‐3p regulate cell proliferation and invasion by targeting CITRON, Claudin10, and androgen receptor signals, thus increasing the efficacy of sorafenib . Apart from these mechanisms, few miRNAs also exploit other cellular pathways to increase sorafenib sensitivity.…”
Section: Micrornas Influencing Sorafenib Response and Their Mechanismmentioning
confidence: 99%
“…64,65 Moreover, miR-486 and miR-367-3p regulate cell proliferation and invasion by targeting CITRON, Claudin10, and androgen receptor signals, thus increasing the efficacy of sorafenib. 66,67 Apart from these mechanisms, few miRNAs also exploit other cellular pathways to increase sorafenib sensitivity. MicroRNA-338-3p sensitizes HCC cells to sorafenib in vitro and in mice models possibly by directly targeting hypoxia-induced factor 1α, hence increasing cell death.…”
Section: Micrornas Increasing Sorafenib Sensitivitymentioning
confidence: 99%